Does government expenditure affect economic growth and people's welfare? : Evidance from North Maluku - Prince Charles Heston Runtunuwu; Zulkefly Abdul Karim (Institute of Computer Science (IOCS), 2023)
The main objective of this research is to test and analyze whether personnel spending, capital spending, goods and services spending, and social assistance spending have an effect on economic growth activities and people's welfare in North Maluku, this is what makes this study important and necessary. Then, also analyze effect of economic growth on welfare. The analysis method using time series data from 2015-2020 and path analysis. The results found local government personnel spending has a significant effect and positively correlated to economic growth of North Maluku. Furthermore, also that government spending has a positive and significant effect on economic growth in North Maluku. The results of the study show that spending on goods and services has a significant effect and is positively correlated to economic growth in North Maluku. The results of this study indicate that social assistance spending has a significant and positive correlation with economic growth in North Maluku. The spending on government employees has an effect on community welfare or the human development index in North Maluku. Furthermore, the results of the study show that government capital spending has no significant effect on the welfare of the people in North Maluku. The results show spending on goods and services has a significant and positive correlation to people's welfare. Then the results of this study indicate that social assistance spending has a significant effect and is positively correlated to the welfare of the people in North Maluku. This means that, if there is an increase in spending on social assistance, it will improve people's living standards